Challenges in servitization of Thai manufacturing companies - pukdeemai, chonnawee (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose: According to the increased pressure in the manufacturing sector in recent yearst, Thailand is potentially losing its competitive advantages to other countries. Thus, a servitization strategy is considered to be one of the methods to maintain the competitiveness, and create additional value for the manufacturing sector of Thailand. There are, however, a few studies regarding servitization within Thailand. This leads to the prevalence of significant gaps in the existing research that needs to be fulfilled. Research design, data and methodology: Qualitative case study research of servitization companies in construction and automotive areas were conducted, and the in-depth interviews with 6 key informants who involve in adopting servitization strategy were investigated to explore the main challenges to be faced, and how to facilitate the successful transition into servitization of the Thai manufacturing company. Results: there are four main phases of challenges in transforming to servitization of the Thai manufacturing industry. Firstly, the design phase that the company must consider both internal and external factors that can affect the need of customers. Secondly, the design stage that are the mindset of employees, the organization structure, working process, and infrastructure need to be changed. Thirdly, the deliver stage is the company needs to find the suitable partner to offer services to the customers. Finally, the company needs to set an appropriate KPI to measure the service performance. Conclusions: customer centric, internal cooperation, and the supplier collaboration are the key factors to be successful in the adopting to servitization Furthermore, the study demonstrated that having a good evaluation plan is also the key factor to be successfully in transformation into servitization of the Thai manufacturing companies.